Does Work Motivation Enhance Job Quality; An Analysis Of The Role Of Employee Experience And Skills - Yulia Efrina; Herman Paleni; Dheo Rimbano (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study examines the effect of work experience and skills on employee output quality, with work motivation as a moderating variable. The study was conducted at the Public Works and Spatial Planning Office of Lubuklinggau City using a quantitative approach and an associative design. All 67 employees were selected as respondents through a saturated sampling technique. Data were collected through questionnaires and analyzed using simple and multiple linear regression and moderation regression analysis (MRA) with the assistance of SPSS. The results indicate that work experience and skills positively and significantly influence output quality, both individually and simultaneously. Additionally, work motivation was found to strengthen the relationship between experience and skills with output quality, suggesting that motivated employees tend to produce higher performance. The limitations of this study include its narrow scope, confined to a single institution, and the limited number of predictor variables. The main contribution of this study is to emphasize the importance of competency development in a work environment that supports motivation. The novelty of this research lies in the use of motivation as a moderating variable in the context of local public sector organizations, which has been rarely studied.